An anomalous pattern of superficial branch of radial nerve - a Cadaveric case report - Mohd Nor, Nurul Huda; San, Aye Aye; Othman, Fauziah (Sociedad Chilena de Anatomia, 2014)
In the present case study, there is an anomalous pattern of superficial branch of radial nerve (SBRN) that can be recognized as an anatomical variant of the left upper limb of a 60 years old donated embalmed male cadaver in the Department of Human Anatomy, Universiti Putra Malaysia, in which the superficial branch of radial nerve supplies the extensor carpi radialis longus and extensor carpi radialis brevis muscle. The superficial branch of radial nerve gave off branch to supply the proximal fusion part of extensor carpi radialis longus and extensor carpi radialis brevis muscles immediately after bifurcation of the radial nerve into the superficial branch of radial nerve and deep branch of radial nerve. This variation is very important to the surgeon as the presence of the variant will make them more careful in dealing with nerve entrapment surgery, reconstructive surgery and in the pain management services, the variation giving indications for treatment.